2017
DOI: 10.1038/s41598-017-18223-y
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and prediction of copper removal from aqueous solutions by nZVI/rGO magnetic nanocomposites using ANN-GA and ANN-PSO

Abstract: Reduced graphene oxide-supported nanoscale zero-valent iron (nZVI/rGO) magnetic nanocomposites were prepared and then applied in the Cu(II) removal from aqueous solutions. Scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy and superconduction quantum interference device magnetometer were performed to characterize the nZVI/rGO nanocomposites. In order to reduce the number of experiments and the economic cost, response surface methodology (RSM) combined with artifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(34 citation statements)
references
References 63 publications
0
26
0
Order By: Relevance
“…The relative influence of the individual variable was calculated by the following Garson equation [ 37 , 38 ]: where I ab is the relative importance of the j th input variable to the output variable; w x is the connection weight; and a , e , and b are the number of neurons in the input layer, hidden layer, and output layer, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The relative influence of the individual variable was calculated by the following Garson equation [ 37 , 38 ]: where I ab is the relative importance of the j th input variable to the output variable; w x is the connection weight; and a , e , and b are the number of neurons in the input layer, hidden layer, and output layer, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Large relative errors are noticed in the P f estimates < 5%, however results indicated that an absolute error and mean absolute error are more appropriate for this estimate. Such a model evaluation metric is commonly used in regression analysis [35] and RSM predictions [36] for percentage quantities. The maximum absolute error in P f prediction is 4% and the MAE is about 2%.…”
Section: Validation Simulationsmentioning
confidence: 99%
“…ANN model was proposed to investigate copper removal from wastewater by adsorption on fungal biomass [27] and cadmium sorption by Shelled Moringa Oleifera Seed Powder from aqueous solution [28]. Moreover, ANN genetic algorithm and particle swarm optimization modeling was used for the prediction of copper removal from aqueous solutions by reduced graphene oxide-supported nanoscale zero-valent iron (nZVI/rGO) magnetic nanocomposites [29]. The Cr(VI) removal efficiency of PIMs cannot be determined by conventional mathematical techniques alone because of non-linear, differential and complicated process.…”
Section: Introductionmentioning
confidence: 99%